MENINGKATKAN KONSENTRASI ANAK DENGAN KEGIATAN MENGANYAM KAIN PERCA PADA ANAK USIA 5-6 TAHUN DI TK TUNAS MUDA KERSIK KEC.MARARANGKAYU KAB. KUTAI KARTANEGARA - Hasnawati - Hasnawati; Mahkamah - Brantasari (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
Concentration is how the child focuses on doing things so that the work can be done within a certain time. While weaving is arranged to sort the arranged sheets in the form of bamboo, paper, rattan, animal skin, or patchwork. This research is motivated by children on 5-6 years old who are still low concentration, especially on children's concentration skills and learning activities is limited to the children's work sheet. In this study the authors propose the problem formulation is whether the weaving patchwork activities can improve the concentration of children on 5-6 years old in Tunas Muda Kindergarten, Kersik Village, Marangkayu District - Kutai Kartanegara. This research used Class Action Research (PTK) in a participative collaborative that aims to improve the concentration of children through patchy weaving activities on children 5-6 years old in Tunas Muda Kindergarten, Kersik Village, Marangkayu District - Kutai Kartanegara. The subjects in this study are 8 children, consisting of 4 men and 4 women. The Object in this study is to increase the concentration of children through weaving patchwork activities. The method used in data collection in this study is observation and documentation, while the techniques and data analysis using qualitative and quantitative descriptive analysis techniques. The results can be seen from the observation of the development in each cycle that in the first cycle average of good value only by 79% and in the second cycle average of 87% with an increase of 8% so that the percentage increase in the concentration of children through children weaving patchwork activities exceed indicator of success is good. It can be concluded that with patchwork weaving activities can increase the concentration of children on 5-6 years old in Tunas Muda Kindergarten, Kersik Village, Marangkayu District Kutai Kartanegara, year of academic 2017/2018.